Project website - Kyriakidis, Phaedon; Lysandrou, Vasiliki; Agapiou, Athos (My University, 2018)
The present document reports on the MedTACH’s project website design and function. Also, the deliverable 4.1 (Project website), comments on the utility of the website, both for the project’s dissemination and also for management purposes. The project’s website is considered one of the most important dissemination tools. The website was designed in such a way, aiming to be simple, functional and intuitive for the project stakeholders’ and different types of audience. The content of the website includes information presenting the project per se (i.e. brief description of MedSTACH’ s objectives, information about the project consortium members), and also project activities and events (i.e. publications and newsletters). The presentation of MedSTACH project and the Centre’s activities in the specific conferences served the networking with key and relevant associations, stakeholders, private agencies, archaeological missions, and universities at a local and international level. The website has been also exploited as a project management tool, via the “Members’ area” (i.e. Intranet), solely accessible by the consortium members. The website has been systematically updated during Phase 1, in order to keep up with the project’s progress.
D4.1 (Project website)
Keywords: Website; MedTACH’s project